2017
DOI: 10.1101/161489
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterising maize viruses associated with maize lethal necrosis symptoms in sub Saharan Africa

Abstract: Maize lethal necrosis disease (MLN) is an emerging disease in East Africa caused by the introduction of Maize chlorotic mottle virus (MCMV). Recent activity seeking to limit spread of the disease is reliant on effective diagnostics. Traditional diagnostics applied on samples with typical field symptoms of MLN have often given negative results using ELISA or PCR for MCMV and Sugarcane mosaic virus (SCMV). Samples collected in the field with typical MLN symptoms were examined using next generation sequencing (NG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…1c) that coalesced and became necrotic after the tasseling stage (data not shown). A kind of synergism in maize involving a potyvirus and MCMV, intensifying symptoms, and increasing damage to the host is known as maize lethal necrosis (Niblett and Claflin 1978), and the involvement of poleroviruses in the disease has been the subject of recent reports (Wamaitha et al 2018;Adams et al 2017). However, here, we did not detect MCMV in any sample, and the synergism was exclusively due to the co-infection of SCMV and MaYMV, as experimentally shown by our studies.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…1c) that coalesced and became necrotic after the tasseling stage (data not shown). A kind of synergism in maize involving a potyvirus and MCMV, intensifying symptoms, and increasing damage to the host is known as maize lethal necrosis (Niblett and Claflin 1978), and the involvement of poleroviruses in the disease has been the subject of recent reports (Wamaitha et al 2018;Adams et al 2017). However, here, we did not detect MCMV in any sample, and the synergism was exclusively due to the co-infection of SCMV and MaYMV, as experimentally shown by our studies.…”
supporting
confidence: 74%
“…R. maidis is a known vector of other poleroviruses, such as barley yellow dwarf virus-RMV (BYDV-RMV) (Rochow 1961) and sugarcane yellow leaf virus (Schenck and Lehrer 2000). Originally described as a luteovirus, BYDV-RMV was later assigned to the genus Polerovirus based on genome sequence analysis and renamed as Maize yellow dwarf virus-RMV (Miller et al 2013;Krueger et al 2016). Luteovirids have a persistent circulative relationship with their vectors (Gray and Gildow 2003), explaining the retention of MaYMV by R. maidis for relatively long periods in the present study.…”
mentioning
confidence: 99%
“…They were 99.4 % similar to MH205607 ( Wamaitha et al, 2018 ) hereby described as MYDMV-RMV from Kenya and MF684367, MaYMV from Ethiopia. They were also 99 % similar to MF974579, a Kenyan isolate ( Massawe et al, 2018 ) and MF425856 Ethiopian isolate ( Adams et al, 2017 ).…”
Section: Resultsmentioning
confidence: 65%
“…The paired-end sequencing yielded 102,169,109 reads (35–151 bp) but 53,297,590 good quality reads were obtained (17–122 bp) after performing quality control. Following contigs assembly and BLASTN identification, most samples strongly showed the presence of MCMV and SCMV while a few samples showed the presence of Maize Yellow Mosaic virus (MaYMV), a recently described polerovirus ( Adams et al, 2017 and Massawe et al, 2018 ). It was also demonstrated that there were no artefactual sequences that were generated in this study for the MCMV, SCMV and MaYMV had significant genome coverage by de novo and reference assemblies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation